Islamic educational thought of Syekh Ali Hasan Ahmad Addary: scientific insight, da’wah strategies and contributions in Indonesia - Pohan, Cindy Aulia; Nasution, Abdusima; Namora, Dian; Hayati, Nursri (UIR Press, 2026)
This study aims to examine the Islamic educational thought of Syekh Ali Hasan Ahmad Addary, focusing on his scientific insight, dawah strategies, and contributions to the development of Islamic education in Padangsidimpuan. This research employs a qualitative descriptive approach using a figure study design within the framework of library research. Data are obtained from previous journal articles as the primary sources and supported by relevant academic books, then analyzed using content analysis techniques. The findings indicate that his scientific insight reflects an integration of Islamic values and rational knowledge, while his da’wah strategies are educational, persuasive, and contextual. His contributions are evident in the development of Islamic educational institutions, the strengthening of educators’ roles, and the enhancement of community intellectual capacity. This study concludes that his educational thought remains relevant in addressing contemporary challenges in Islamic education. However, this research is limited to literature-based sources. The originality of this study lies in its integrated analysis of a local scholar’s thought across three main dimensions: scientific insight, da’wah strategies, and educational contributions.